Psychological Capital Mediates the Relationship Between Problematic Smartphone Use and Learning Burnout in Chinese Medical Undergraduates and Postgraduates: A Cross-Sectional Study - Zhang, Changhong; Li, Ge; Fan, Zhaoya; Tang, Xiaojun; Zhang, Fan (Frontiers in Psychology, 2021)
Learning burnout is a pressing issue among Chinese medical students and has drawn continuous attention worldwide. Studies have found that mobile phone addiction may have a mediating effect on learning burnout, but more research is needed in this direction. Furthermore, studies have also focused on the mediating effect of psychological capital on the relationship between mobile phone addiction and learning burnout. The present study was a cross-sectional survey that recruited 1800 participants from a medical university in Chongqing, China using convenience sampling. A questionnaire based on the Mobile Phone Addiction Tendency Scale, Psychological Capital Questionnaire, Learning Burnout Scale, and demographic variables were administered to these students, and 1475 provided valid responses (81.94%). Hierarchical regression and the bootstrap method were used to examine the mediating effect of psychological capital. After controlling for demographic variables, mobile phone addiction was positively correlated with learning burnout (β = 0.366, p < 0.01), psychological capital was negatively related to mobile learning burnout (β = -0.288, p < 0.01), and mobile phone addiction was negatively correlated with psychological capital (β = -0.250, p < 0.01). In all four mediation models, the lower and upper bounds of the confidence intervals (CI) did not contain 0. Psychological capital mediates the relationship between mobile phone addiction and learning burnout among Chinese medical students.